Radiocarbon chronology of archeological sites in South-eastern Europe - Obelić, Bogomil (Array, 1999)
Results of 14C measurements of samples from various archaeological sites in SE Europe, spanning from Mesolithic to the Middle Ages, are presented. Radiocarbon results were calibrated by using the Oxford University OxCal program.